Optic neuritis and multiple sclerosis. - Ebers, G (1985)
Isolated demyelinative ON is a forme fruste of MS: adequately screened ON cases should be included in MS epidemiologic and family studies. In typical cases the diagnosis remains clinical. Evoked responses and CSF studies are helpful. The presence of oligoclonal banding is of predictive value for the subsequent development of MS.